Influence of Fucoidan in Mucus Thickness of Gastric Mucosa in Patients with Chronic Gastritis - Kaka Renaldi; Marcellus Simadibrata; Ari Fahrial Syam; Abdul Aziz Rani; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Chronic gastritis is commonly found with complains of dyspepsia, which may decrease work productivity. Imbalance between agressive and defensive factors is the cause of chronic gastritis. Therapy is mostly directed to the agressive factors, particularly gastric acid and very few studies are directed on defensive factors. Mucus is the first defense mechanism of gastric mucosa. Fucoidan is a phytopharmaca, which is thought to increase the thickness of gastric mucosa. The objective of this study was to know the thickness of gastric mucosa in patients with chronic gastritis and to evaluate the effect of fucoidan to the gastric mucosa thickness in patients with chronic gastritis. Method: In this double-blinded randomized clinical trial study, 41 patients in the Endoscopy Unit Cipto Mangunkusumo Hospital between October 2009 and October 2010 were enrolled consecutively. Selected patients were divided into 2 groups: a group was given fucoidan and another group was given placebo. Statistical analysis was done using T-test. Results: Of 41 chronic gastritis patients, only 34 patients completed this study. There was difference of mucus thickness of gastric mucosa in patients with chronic gastritis; in the antrum 42.59 µ m (± 8.67) and in the corpus 44.28 µ m (± 9.64). This study also showed that fucoidan administration increased the mucus thickness in the antrum by 7.42 µ m and in the corpus by 7.74 µ m compared to placebo significantly. Conclusion: Fucoidan increased the mucus thickness of gastric mucosa in patients with chronic gastritis. Keywords: mucus thickness, chronic gastritis, fucoidan